Mikrobiološke preiskave v diagnostiki sepse - Müller-Premru, Manica (Zdravniški vestnik, 2013)
Background:Sepsis is one of the most serious bacterial infections. The diagnosis of sepsis is clinical. Microbiologists can detect bacteremia, which however is not present in all septic patients, by the procedure called blood culture.Methods:Blood culture is a semi-automated procedure of culturing blood in liquid media to detect and identify the causative agents. It is important to take 2 to 3 blood cultures with adequate volume of blood. The new, faster methods for bacterial identification from positive blood cultures and molecular methods for the detection of bacterial DNA directly from a blood sample are also becoming available.Results:In the years 2006 to 2011, the number of blood cultures obtained from patients in the University Medical Centre in Ljubljana, Institute of Oncology and the General hospital of Trbovlje (from 2007) was constantly increasing, from 18,404 in 2006 to 25,214 in 2011. The number of patients with positive blood culture/s increased from 1,033 in 2006 to 1,396 in 2011. The rate of blood culture positivity ranged from 10.9 % to 12.3 %. The ratio between gram-positive and gram-negative bacteria was approximately 50:50 %. In all the years under study, Escherichia coliwas the most frequent pathogenic isolate (19.2 % to 22.9 %), followed by Staphylococcus aureus(15.3 % to 17.4 %). Klebsiellaspp. represented 5.3 % to 8.3 % of isolates, Pseudomonas aeruginosa1.8 % to 3.4 %, Streptococcus pneumoniae2.9 % to 4.7 %, Enterococcusspp. 5.4 % to 8.1 %, anaerobes 2.1 % to 3.2 %. Coagulase-negative staphylococci decreased from 23.3 % to 16.9 %. Today, bacteria are identified by the fast and accurate method of mass spectrometry. Bacteria can alternativelly be detected directly from blood by the molecular tests.Conclusions:Blood culture is a very common procedure, its rate of positivity is stable. Among bacteria, the number and the proportion of pathogenic bacteria such as E. coli, S. aureusand S. pneumoniaeis increasing and the proportion of contaminants is decreasing.
Keywords: bacteremia; bakteriemija; epidemiologija; epidemiology; sepsa; sepsis